EFFECT OF ATMOSPHERIC MASSES ON THE SPECTRAL INTENSITY OF SOLAR RADIATION - Nikitin, B.; Mayorov, V.; Kharchenko, V. (Енергетика і автоматика, 2016)
The effect of the atmospheric mass on the way to the sunlight receiving surface on the spectral characteristics of solar radiation in the atmospheric layer under consideration AM 1.5 as a filter having appropriate transmittance for the corresponding wavelength.